Comprehensive analysis of morphology, transcriptomics, and metabolomics of banana (Musa spp.) molecular mechanisms related to plant height - Wei, Junya; Liu, Guoyin; Sun, Mingzhen; Wang, Hao; Yang, Ping; Cheng, Shimin; Huang, Lina; Wei, Shouxing; Liu, Debing (Frontiers in Plant Science, 2025)
IntroductionPlant height is an important agronomic trait that not only affects crop yield but is also related to crop resistance to abiotic and biotic stresses.MethodsIn this study, we analyzed the differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs) between Brazilian banana and local dwarf banana (Df19) through transcriptomics and metabolomics, and combined morphological differences and endogenous hormone content to analyze and discuss themolecular mechanisms controlling banana height.ResultsSequencing data showed that a total of 2851 DEGs and 1037 DAMs were detected between Brazilian banana and local dwarf banana (Df19). The main differential biological pathways of DEGs involve plant hormone signaling transduction, Cutin, suberin and wax biosynthesis, phenylpropanoid biosynthesis, mitogen-activated protein kinase (MAPK) signaling pathway in plants, amino sugar and nucleotide sugar metabolism, etc. DAMs were mainly enriched in ATP binding cassette (ABC) transporters, amino and nucleotide sugar metabolism, glycerophospholipid metabolism, lysine degradation, and phenylalanine metabolism.DiscussionOur analysis results indicate that banana plant height is the result of the synergistic effects of hormones such as abscisic acid (ABA), gibberellic acid (GA3), indole-3-acetic acid (IAA), jasmonic acid (JA), brassinosteroids (BR) and other plant hormones related to growth. In addition, transcription factors and ABC transporters may also play important regulatory roles in regulating the height of banana plants.